Keeping Up with the Outcomes-Based Education Trends in Nursing Education and Practice Among Professionals in the National Capital Regiona Dissertation Conferred in January 2024 - Ranada, Joan O.; Lily Famadico (Future Science / FSH-PH Publications, 2025)
Nursing as a caring profession is constantly evolving as the call for international Healthcare demands are consequently in progress. The study aimed to determine how professional nurses are keeping up with Outcomes-Based Education trends in nursing education and practice. The study employed Exploratory Sequential Mixed Methods Design comprising of five phases namely: 1) Integrative Literature Review; 2) PICO: Writing the Integrative Review; 3) Tool Development and Testing – Quantitative; 4) Framework Development; 5) Functionality Evaluation from Expert Interviews – Qualitative. Emergent themes based on reviewed related literature were: 1) Core of Nursing; 2) Quality Patient Care; 3) Professional Transfiguration; 4) Excellence in Health Care. J.O.R.-O.B.E. Measurement Tool was developed and pilot-tested with 0.80 to 0.92 acceptability level. Respondents were selected by purposive sampling. Results revealed that professional nurses who graduated under OBE curriculum were very satisfactorily keeping up with overall mean of 4.32, with a provision on research engagement and community-based staff development programs. Utilizing T-test statistical tool, data shown insignificant differences in the average performance of nurses as perceived by charge nurses, head nurses, nurse supervisors and staff nurses with a p-value of 0.368 . Moreover, the developed J.O.R.-O.B.E. framework was evaluated by the chief nurses as an Excellent, Effective, and Highly Recommended.The findings of the study shed significant implications towards nursing profession. Utilization of J.O.R.-O.B.E. Measurement Tool and J.O.R.-O.B.E. Framework can serve to support the nursing workforce, for institutions to achieve excellent health care and cope up with global demands.